Zimbabwean pre-clinical medical students use of deep and strategic study approaches to learn anatomy at two new medical schools - Zilundu, Prince L. M.; Chibhabha, Fidelis; Chengetanai, Samson; Fu, Rao; Zhou, Li-Hua (Wiley, 2022)
Anatomy is a challenging preclinical subject owing to the vast amount of information that students need to master. The adoption of relevant study approaches is key to the development of a long-lasting understanding of anatomical subject matter. Phenomenographic educational research describes the medical students as using a variable mix of deep, strategic, and surface approaches to study. Continually assessing students' learning preferences and approaches is crucial for achieving the desired learning outcomes. The approaches to studying anatomy in two groups of first-year Zimbabwean medical students from two newly established medical schools were collected using the Approaches and Study Skills Inventory for Students (ASSIST) instrument and than analyzed. At least 90% of the students believed that anatomy involved reproducing knowledge or personal understanding and development. Overall, the majority of the students adopted deep and strategic approaches, while a distant minority used the surface approach. There was no significant correlation between either the students' sex or age and their preference for a specific approach to studying. The mean anatomy grades for students using a strategic approach were significantly higher than those using deep or surface approaches. The number of strategic learners was double that of deep learners among the high achievers subgroup. The strategic approach positively correlated with performance in examinations. Generally, the students shared a common understanding of the concept of anatomy learning. Studies such as this can assist with the identification of students at risk of failure and empower lecturers to recommend the adoption of more beneficial strategic and deep learner traits.